Mednarodna znanstvena konferenca 200-letnica rojstva Franca Miklošiča in Miklošičeva monografija: Ob dvestoletnici rojstva Franca Miklošiča. Ur. Marko Jesenšek. Ljutomer: Gimnazija Franca Miklošiča Ljutomer, 2013. 487 str. - Horvat, Mojca (Slavia Centralis, 2020)
The author of the article reports on an international scientific conference in honor of the bicentennial of Miklošič’s birth and on a monograph published on the occasion of the event.